JEJARING USAHA “RASENDRIYA KRIYA TULANG DAUN” SEBAGAI STRATEGI KEBERLANJUTAN PROGRAM PENGEMBANGAN USAHA PRODUK INTELEKTUAL KAMPUS - Amin RETNONINGSIH; Widowati Widowati; Muhammad KHAFID; Sucihatiningsih Dian Wisika PRAJANTI (Pusat Pengabdian kepada Masyarakat- LPPM Universitas Terbuka, 2021)
Woody tree leaves have diverse shapes and repeats. The skeleton leaves in the woody plant group are quite strong and have a unique shape so that they can become as the raw material for making exclusive crafts. Raw materials of skeleton leaves have been used by the business unit